Artemether and Lumefantrine Loaded Self-nanoemulsifying drug Delivery System for Enhancement of Bioavailability - Prasad, Rao Monica Raghavendra; A, Pardeshi Amol (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: This study involves development and evaluation of bioavailability of oral self-nanoemulsifying drug delivery system of BCS class II and IV drugs, Artemether and Lumefantrine (AL), respectively. This fixed combination is used for treatment of drug resistant malaria. Self nanoemulsifying drug delivery system (SNEDDS) was developed due to lipophilicity of both drugs. Pseudo ternary phase diagrams were derived based on solubility of drugs in oils and surfactants for identifying self-nanoemulsifying region. Materials and Methods: Propylene glycol dicaprylate caprate, Cremophor EL, Tween 80 (1:1) and Transcutol HP were selected as oil and surfactants. Pseudo ternary plots were constructed based on solubility of AL in oils and surfactants to identify composition of formulations. They were evaluated for self-emulsification time, percent transmittance, cloud point, thermodynamic stability and in vitro release. Globule size analysis was done using Malvern Zeta sizer. Pharmacokinetic parameters like area under curve (AUC), Cmax and Tmax were evaluated using Wistar rats. Results and Discussion: All formulations displayed globule size between 27-32 nm while percent transmittance was between 90-99%. Cloud point above 37ºC was indicative of integrity of self-nanoemulsifying properties in vivo. Cumulative percent release in 1 hr in 0.1 N HCl was in range of 75 to 100 %. A two-fold enhancement in bioavailability was observed with SNEDDS as compared to plain drugs. AUC0–5h were increased by 2 times for artemether and 1.71 times for lumefantrine compared to plain drug suspensions. This proved the prospective use of SNEDDS to improve dissolution and oral bioavailability for poorly water-soluble antimalarial drugs.
Keywords: Artemether; Lumefantrine; Low oral bioavailability; Self-nanoemulsifying; drug delivery system; In vitro dissolution